If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 37 + -1X = 14 Solving 37 + -1X = 14 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-37' to each side of the equation. 37 + -37 + -1X = 14 + -37 Combine like terms: 37 + -37 = 0 0 + -1X = 14 + -37 -1X = 14 + -37 Combine like terms: 14 + -37 = -23 -1X = -23 Divide each side by '-1'. X = 23 Simplifying X = 23
| 48-6x=4x-2 | | 8-g= | | X+150=.75(x+150) | | 3(4x-9)+12=9 | | 5t-7=5t | | 2a+14=-2(-a-3) | | -m-9=15 | | -I-17I= | | 3d-15=3(5+d) | | 11x+2x-9=24 | | 3(4x-9)12=9 | | -2(2a-7)=14-4a | | 3x+8x=9 | | 4x^2+25=7 | | 4a+45+4a+45=31a-2 | | 2x+6+5x=20 | | -7+2x+3=3x+5+2x | | -3+b(x+4)=47 | | 3p-p-5p=-3p-6 | | 7y-6x=72 | | 10+2b=76.50 | | -3(y-2)=6-3y | | 9x-6x+4=-20 | | Y=4cos(6x) | | 56+28x= | | 16-4b=2(8-2b) | | 6*6-(7+5)= | | 3x^2+5x=11 | | -9=27-11p-13b | | 17=-2w-5 | | wz+5xy=8v | | 5-8abs(-2n)=-75 |